The impact of soil and rock mining on freshwater provisioning services in Peniraman Village, Mempawah Regency, West Kalimantan - Boy Rangga; Aji Ali Akbar; Henny Herawati (Brawijaya University, 2022)
Various human activities can affect ecosystem services, including mining activities. Since 1960, Peniraman Village has been known for its soil and rock mining. Mining increases the risk of environmental degradation by increasing the demand for freshwater provisioning services. This study aims to assess the impact of damage from mining in Peniraman Village on groundwater potential and the environment's carrying capacity based on ecosystem service. Ecosystem services are analyzed using two determinants: land cover and landscape, with a spatial method. This study resulted in a large forest change between 1972 and 2020, which was estimated to lose 16.5 hectares of forest each year, whereas Peniraman Village will lose its forest in 26 years. There was also a land conversion in primary swamp forests into open land for various community activities from 1972-2020, mostly agriculture, settlement, and plantation. On the other hand, the mining area will be exhausted in 30-40 years given the current mining rate. These actions shifted the class of groundwater provisioning services from very high to very low. The water potential was calculated based on the ecosystem services that have intermediate and low-level class potential in Peniraman Village of 1,077.98 hectares, or 48.15% of the total area. Although 48.6 percent of the Peniraman Village area is still within the safe level for water availability based on supply and demand, the government and community should pay close attention to this issue to avoid further harm.